ADHD and autism symptoms in youth: a network analysis. (13th May 2021) - Farhat, Luis C.; Brentani, Helena; de Toledo, Victor Hugo Calegari; Shephard, Elizabeth; Mattos, Paulo; Baron‐Cohen, Simon; Thapar, Anita; Casella, Erasmo; Polanczyk, Guilherme V.
Abstract : Background: Previous research investigating the overlap between attention‐deficit/hyperactivity disorder (ADHD) and autism spectrum disorder (henceforth, autism) symptoms in population samples have relied on latent variable modeling in which averaged scores representing dimensions were derived from observed symptoms. There are no studies evaluating how ADHD and autism symptoms interact at the level of individual symptom items. Methods: We aimed to address this gap by performing a network analysis on data from a school survey of children aged 6–17 years old ( N = 7, 405). ADHD and autism symptoms were measured via parent‐report on the Swanson, Nolan, Pelham‐IV questionnaire and the Childhood Autism Spectrum test, respectively. Results: A relatively low interconnectivity between ADHD and autism symptoms was found with only 10.06% of possible connections (edges) between one ADHD and one autism symptoms different than zero. Associations between ADHD and autism symptoms were significantly weaker than those between two symptoms pertaining to the same construct. Select ADHD symptoms, particularly those presenting in social contexts (e.g. 'talks excessively', 'does not wait turn'), showed moderate‐to‐strong associations with autism symptoms, but some were considered redundant to autism symptoms. Conclusions: The present findings indicate that individual ADHD and autism symptoms are largely segregated in accordance with diagnostic boundaries corresponding to these conditions in children and adolescents from the community. These findings could improve our clinical conceptualization of ADHD and autism and guide advancements in diagnosis and treatment.